Didacticization Of Complex Thinking In Language Teaching - Laadjal ,Salah (University of Eloued جامعة الوادي, 2024)
In our study, we have delved into the integration of complex*thinking within language education, drawing from the perspective of Edgar Morin. We have explored various facets of this integration, elucidating pedagogical approaches, instructional methods, learner assessment, and teacher training. Focusing on the theoretical underpinnings, we have elucidated the pivotal tenets of Edgar Morin's complexity theory, notably multidimensionality, recursion, and interaction. We have probed how complex*thinking can be operationalized in language instruction to engender a more profound comprehension of languages and the processes of learning. Furthermore, we have engaged in discourse concerning formative and reflective evaluation, a practice fostering metacognition among learners. The thorough examination of teacher training has also been undertaken, encompassing the presentation of training programs centered around complex* thinking. Keywords: ; ; ; ; pedagogical approaches
Perspectives And Practices
Keywords: language education; learner assessment; teacher training; complex thinking